Pharmacovigilance Studies Of Commonly Encountered Adverse Drug Reactions Reported From M.K.C.G. Medical College& Hospital, Berhampur - Mishra, Sailen Kumar; Rath, Bandana; Sahu, Yajnesh Prasanna (Journal of Neonatal Surgery, 2025)
Background: The relevance of Pharmacovigilance to adverse drug reaction(ADR) detection is highlighted worldwide. Pharmacovigilance starting from the tip of clinical trial in industries up to post -marketing surveillance is essential to ensure the drug safety. As newer drugs are entering market at a rapid pace pharmacovigilance with special attention to monitor and report adverse drug reaction is today’s need. Objective: This study on adverse drug reaction monitoring and reporting was carried out in collaboration the departments of dermatology, psychiatry, pediatrics, radiotherapy of MKCG Medical College, Berhampur. Data obtained from this study may throw some light in the network of pharmacovigilance and bring a change in the safety data profile of established as well as upcoming drugs Methods: This was a prospective, observational study, carried from January 2013 to October 2014 in collaboration with department of dermatology, psychiatry, paediatric and radiotherapy of MKCG Medical College and hospital (tertiary care hospital). Incidence rate for occurrence of adr were calculated using MS office excel 2010. Column statistics expressing mean, standard deviation, median, range, confidence interval, for different parameters of ADRs were calculated using a statistical software, Graphpad prism version 5.0. Results: Out of 237 ADR cases 90 were cutaneous ADRs. Among the various patterns of Cutaneous adverse drug reactions (CADRs), the major presentations were exfoliative dermatitis (n= 17; 18.89%), Fixed drug eruption (n= 17;78%) and 15.56% of them were urticarial rashes. Drugs suspected to cause CADR in the study population were broadly classified in 10 groups. Among them 26.67% of CADR were caused by various NSAIDs. In this study, a total of 9900 patients attending psychiatry OPD were screened for ADR. Out of which 60 patients were suspected at least one ADR (0.61%). Seven major different kinds of psychotropic drugs were used for different kind of psychiatry illness. Extrapyramidal side effects was the commonest ADR (n=41; 34.17%) reported followed by weight gain (n=35; 29.17%). Anticholinergic side effects and sedation were observed in 16.17% and 10.83% of cases respectively. In this study period total 57 paediatric patients reported with different ADRs. Among them 61.40% patients were male and 38.60% were female. The commonest drug to develop ADR was ofloxacin (26.28%) followed by diclofenac (14.04%). Only 12.28% of ADR were with Ceftriaxone and metronidazole. During this study period a total 326 patients received different cancer chemotherapeutic agents among which 30 patients (9.22%) developed various ADRs. The most common ADR was nausea and vomiting (53.33%), hematological ADR (40%), hepatotoxicity skin rash and diarrohea were least to occur. Conclusion: The patterns of the adverse drug reactions and the drugs which caused them, varied in our study according to the different pattern of the drug intake, the associated illness and the susceptibility of the patients. This study was able to recognize the ADRs within a short period and was limited to a solitary institute. Yet, the results convincingly prepare for the edifice to lead us to further long term active surveillance in early detection of ADRs and drug safety. Further study in collecting ADRS with drugs used in special situations, population and drug interactions is an immense need.